Introduction and Socialization of the SMART SOP (Standard Operating Procedure) Application to Malang Community Health Center Nurses - Apryanto, Frengki (STIKes Patria Husada Blitar, 2024)
Technology in health services, both in hospitals and community health centers, plays an important role in increasing the effectiveness and efficiency of nurses' performance. One of the technological supports is the use of the SMART SOP application so that nurses' tasks can be effective, and efficient and reduce the risk of errors thereby improving the quality of service. The targets for this activity were Malang Community Health Center nurses. This activity aimed to increase knowledge and skills in using the SMART SOP application. The methods used include lectures, discussions, and simulations of application use. Include The results showed an increase in knowledge from an average score of 60.2 to 96.4 and the Mann-Whitney test shows p-value=0.000, which meant there was an influence of community service program on target knowledge. Meanwhile, skills in using the SMART SOP application on average increased to 85. The knowledge and skills possessed by nurses are important factors in adopting the use of SMART SOP in the workplace. With a good understanding of the working principles of SOPs and technological skills, nurses can more easily understand and implement procedures based on smart SOPs.